Friction and wear properties of Cu-CuG nanocomposite fabricated by accumulative roll bonding - M. Rahimi; A. R. Eivani; H. R. Jafarian (Scientific Reports)
Abstract This study investigates the effect of contact force on the friction and wear behavior of copper-graphene (Cu-CuG) nanocomposites against AISI 52,100 steel. Pin-on-disk dry sliding wear tests were conducted under normal forces of 10 and 30 N, with a sliding distance of 1000 m and a linear speed of 0.1 m/s. Worn surfaces of the Cu-CuG samples, AISI 52,100 steel counterbodies and subsurface beneath the wear track were analyzed using field emission scanning electron microscopy (FESEM) and energy-dispersive spectroscopy (EDS). The results show that normal force significantly influence wear resistance at higher ARB cycles. Cu-CuG nanocomposites fabricated after two ARB cycles exhibited the highest wear resistance compared to the initial sample, with a wear volume of 0.82 mm3 and 2.14 mm3 under 10 and 30 N force, respectively. However, increased ARB cycles led to reduced wear resistance due to delamination wear, driven by strain incompatibility and an increased number of interfaces. The coefficient of friction (CoF) was lowest after two ARB cycles (0.5) under a 10 N load, which can be attributed to the graphene’s lubricating effect. However, with additional ARB cycles, the CoF increased due to the accumulation of wear debris. Furthermore, increasing the normal load led to higher CoF values in the nanocomposites, primarily due to the enlarged contact area and greater generation of wear debris under higher contact pressures. SEM analysis of the counterbodies revealed minor abrasive wear on the AISI 52,100 steel pins, along with material transfer from the Cu-CuG composites.